2020
DOI: 10.1007/s12103-020-09530-8
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Trauma and Parenting Practices in Internet Crimes against Children Task Force Investigators

Abstract: Investigating cases of child pornography requires daily exposure to sexually explicit material involving children and may have negative implications on the mental wellbeing of those in this line of work. This study aimed to identify whether secondary traumatic stress symptoms were associated with participants' parenting behaviors and concerns about their own children's use of the internet. Internet Crimes Against Children Task Force workers (n = 212) completed online questionnaires measuring work exposure to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Consistent with prior ndings (Bourke & Craun, 2014a;Brady, 2017;Perez et al, 2010;Vang et al, 2020) and in alignment with the JD-R model (Bakker et al, 2023;Schaufeli & Bakker, 2004), prolonged exposure poses a threat to health, leading to posttraumatic stress disorder. This indicates that the daily confrontation, inherent in the work role (Brady, 2017;Stewart & Witte, 2020), serves as a source of long-term posttraumatic stress. Additionally, by extending previous measurements of exposure (Brady, 2017;Perez et al, 2010), we highlight that intensity is as relevant as frequency for investigators.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with prior ndings (Bourke & Craun, 2014a;Brady, 2017;Perez et al, 2010;Vang et al, 2020) and in alignment with the JD-R model (Bakker et al, 2023;Schaufeli & Bakker, 2004), prolonged exposure poses a threat to health, leading to posttraumatic stress disorder. This indicates that the daily confrontation, inherent in the work role (Brady, 2017;Stewart & Witte, 2020), serves as a source of long-term posttraumatic stress. Additionally, by extending previous measurements of exposure (Brady, 2017;Perez et al, 2010), we highlight that intensity is as relevant as frequency for investigators.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, we re ne existing research by distinguishing between exposure and empathy for suffering, categorizing exposure as a work-related trauma confrontation (Fischbach, 2020;Kleineidam & Fischbach, 2023). Exposure to disturbing material is an inherent and essential task in internet child exploitation investigation (Brady, 2017;Stewart & Witte, 2020). However, prolonged exposure to traumatic experiences of child abuse at work can directly lead to posttraumatic stress disorder in the long run (American Psychiatric Association, 2013), previously identi ed as an indirect or secondary form of traumatization (Parkes et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…CSAE officers and staff have reported desensitisation, intrusive thoughts, increased hypervigilance, suspiciousness and overprotectiveness ( Perez et al, 2010 ; Powell et al, 2015 ; Parkes et al, 2018 ), particularly in relation to their own children ( Stewart and Witte, 2020 ; Tapson et al, 2021 ). In their development of a traumatic events checklist for police, Miller et al (2021) asked police officers to rank their work-related traumatic events and found that the most populated category involved children, and included fatalities, abuse and sexual exploitation.…”
Section: Introductionmentioning
confidence: 99%